Speckle interferometry of secondary components in nearby visual binaries - Tokovinin, Andrei; Horch, Elliott P (The Astronomical Journal, 2016)
Statistical characterization of secondary subsystems in binaries helps to distinguish between various scenarios of multiple-star formation. The Differential Speckle Survey Instrument was used at the Gemini-N telescope for several hours in 2015 July to probe the binarity of 25 secondary components in nearby solar-type binaries. Six new subsystems were resolved, with meaningful detection limits for the remaining targets. The large incidence of secondary subsystems agrees with other similar studies. The newly resolved subsystem HIP 115417 Ba,Bb causes deviations in the observed motion of the outer binary from which an astrometric orbit of Ba,Bb with a period of 117 years is deduced. © 2016. The American Astronomical Society. All rights reserved.
17 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/112-209-617-018-947 tex.type: [object Object]
Keywords: binaries: visual; dept.phy; peer-reviewed; stars: low-mass

Speckle observations and orbits of multiple stars. - Tokovinin, Andrei; Everett, Mark E; Horch, Elliott P; Torres, Guillermo; Latham, David W (Astronomical Journal, 2019)
We report results of speckle-interferometric monitoring of visual hierarchical systems using the newly commissioned instrument NN-EXPLORE Exoplanet and Stellar Speckle Imager at the 3.5 m WIYN telescope. During one year, 390 measurements of 129 resolved subsystems were made, while some targets were unresolved. Using our astrometry and archival data, we computed 36 orbits (27 for the first time). Spectro-interferometric orbits of seven pairs are determined by combining positional measurements with radial velocities measured, mostly, with the Center for Astrophysics digital speedometers. For the hierarchical systems HIP 65026 (periods 49 and 1.23 yr) and HIP 85209 (periods 34 and 1.23 yr) we determined both the inner and the outer orbits using astrometry and radial velocities and measured the mutual orbit inclinations of 11.°3 ± 1.°0 and 12.°0 ± 3.°0, respectively. Four bright stars are resolved for the first time; two of those are triple systems. Several visual subsystems announced in the literature are shown to be spurious. We note that subsystems in compact hierarchies with outer separations less than 100 au tend to have less eccentric orbits compared to wider hierarchies. © 2019. The American Astronomical Society. All rights reserved..
13 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/097-296-370-783-044 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; ⛔ No DOI found

Speckle Interferometry at SOAR in 2018 - Tokovinin, Andrei; Mason, Brian D.; Mendez, Rene A.; Horch, Elliott P.; Briceño, Cesar (The Astronomical Journal, 2019)
The results of speckle interferometric observations at the 4.1 m Southern Astrophysical Research Telescope (SOAR) in 2018 are given, totaling 3097 measurements of 2427 resolved pairs with separations from 11 mas to 5.″9 (median 0.″15, magnitude difference up to 7 mag) and nonresolutions of 624 targets. This work continues our long-term speckle program. Its main goal is to monitor orbital motion of close binaries, including members of high-order hierarchies and Hipparcos pairs in the solar neighborhood. Also, pre-main-sequence stars in the Orion OB1 association were surveyed, resolving 26 out of 118 targets. In addition, we report the discovery of 35 new companions among field visual multiples (some of which are likely optical) and first-time resolutions of another 31 pairs. By combining the measurements given here with the published ones, we computed 76 orbits for the first time and updated orbital elements of 34 visual binaries. Their periods range from 0.65 to 1100 yr, and their quality varies from first tentative solutions of grade 5 to accurate elements of grades 1 and 2. Finally, a list of 53 spurious pairs discovered by various techniques and unresolved at SOAR is given. © 2019. The American Astronomical Society. All rights reserved..
28 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/174-863-467-125-303, pop00135 tex.type: [object Object]
Keywords: dept.phy; material: machine-readable tables; peer-reviewed

Speckle interferometry at SOAR in 2016 and 2017 - Tokovinin, Andrei; Mason, Brian D.; Hartkopf, William I.; Mendez, Rene A.; Horch, Elliott P. (The Astronomical Journal, 2018)
The results of speckle interferometric observations at the 4.1 m Southern Astrophysical Research Telescope in 2016 and 2017 are given, totaling 2483 measurements of 1570 resolved pairs and 609 non-resolutions. We describe briefly recent changes in the instrument and observing method and quantify the accuracy of the pixel scale and position angle calibration. Comments are given on 44 pairs resolved here for the first time. The orbital motion of the newly resolved subsystem BU 83 Aa,Ab roughly agrees with its 36-year astrometric orbit proposed by J. Dommanget. Most Tycho binaries examined here turned out to be spurious. © 2018. The American Astronomical Society. All rights reserved..
30 citations (Crossref) [2023-10-31]
Keywords: binaries: visual; dept.phy; peer-reviewed

Speckle interferometry at SOAR in 2015 - Tokovinin, Andrei; Mason, Brian D; Hartkopf, William I; Mendez, Rene A; Horch, Elliott P (The Astronomical Journal, 2016)
The results of speckle interferometric observations at the Southern Astrophysical Research Telescope in 2015 are provided, totaling 1303 measurements of 924 resolved binary and multiple stars, and non-resolutions of 260 targets. The separations range from 12 mas to 3.″37 (median 0.″17); the maximum measured magnitude difference is 6.7 mag. We resolved 27 pairs for the first time, including 10 as inner or outer subsystems in previously known binaries, e.g., the 50 mas pair in Cha. Newly resolved pairs are commented upon. We discuss three apparently non-hierarchical systems that have been discovered in this series, arguing that their unusual configurations are the result of projection. The resolved quadruple system HIP 71510 is also studied. © 2016. The American Astronomical Society. All rights reserved..
38 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-730-326-407-996 tex.type: [object Object]
Keywords: binaries: general; dept.phy; peer-reviewed

Speckle interferometry at soar in 2014 - Tokovinin, Andrei; Mason, Brian D; Hartkopf, William I; Mendez, Rene A; Horch, Elliott P (The Astronomical Journal, 2015)
The results of speckle interferometric observations at the Southern Astrophysical Research Telescope (SOAR) telescope in 2014 are given. A total of 1641 observations were taken, yielding 1636 measurements of 1218 resolved binary and multiple stars and 577 non-resolutions of 441 targets. We resolved for the first time 56 pairs, including some nearby astrometric or spectroscopic binaries and ten new subsystems in previously known visual binaries. The calibration of the data is checked by linear fits to the positions of 41 wide binaries observed at SOAR over several seasons. The typical calibration accuracy is 0.°1 in angle and 0.3% in pixel scale, while the measurement errors are on the order of 3 mas. The new data are used here to compute 194 binary star orbits, 148 of which are improvements on previous orbital solutions and 46 are first-time orbits. © 2015. The American Astronomical Society. All rights reserved..
81 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/016-545-424-948-585 tex.type: [object Object]
Keywords: binaries: general; dept.phy; peer-reviewed

Observations of binary stars with the Differential Speckle Survey Instrument. VIII. Measures of metal-poor and triple stars from 2015 to 2018 - Horch, Elliott P.; Tokovinin, Andrei; Weiss, Samuel A.; Löbb, János; Casetti-Dinescu, Dana I.; Granucci, Nicole M.; Hess, Nicole M.; Everett, Mark E.; van Belle, Gerard T.; Winters, Jennifer G.; Nusdeo, Daniel A.; Henry, Todd J.; et al. (The Astronomical Journal, 2019)
We present 248 speckle observations of 43 binary and 19 trinary star systems chosen to make progress in two main areas of investigation: the fundamental properties of metal-poor stars and star formation mechanisms. The observations were taken at the Gemini North and South telescopes during the period 2015 July to 2018 April, mainly with the Differential Speckle Survey Instrument but also with a few early results from the new 'Alopeke speckle camera at Gemini North. We find that the astrometry and photometry of these observations as a whole are consistent with previous work at Gemini. We present five new visual orbits for systems important in understanding metal-poor stars, three of which have orbital periods of less than 4 yr, and we indicate the degree to which these and future observations can impact our knowledge of stellar properties and star formation. In particular, we find a decrease in mass at fixed spectral type for metal-poor stars versus their solar-metallicity analogs that is consistent with predictions that are made from current stellar models. © 2019. The American Astronomical Society. All rights reserved..
19 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/073-502-692-786-428, pop00025 tex.type: [object Object]
Keywords: binaries: visual; dept.phy; peer-reviewed; stars: individual; techniques: high angular resolution; techniques: interferometric; techniques: photometric